An Exploratory Study of Western Cape Province NonProfit Organisations response to the COVID-19 Pandemic - Tinnion, Charlotte (Department of Social Development, 2023)
This study focuses on the response of NPOs to the COVID-19 pandemic. The main research questions focus on the role of NPO leaders and management in responding to the COVID-19 pandemic. The effect of COVID-19 on the organisations' operations, focusing on service delivery, staff and finances are explored. The study looks at the lessons learned by the NPO sector considering the COVID-19 pandemic, focusing on factors that enabled NPOs to survive (protective factors) and factors that placed NPOs at risk of closure (risk factor). Change Management Theory and Organisation Resilience Theory are used as two theoretical frameworks that underpin the study. The research paradigm of the study is qualitative and the research design and method is exploratory. The exploratory nature of qualitative research was selected given that the COVID-19 pandemic is a recent and hitherto minimally research area with limited information. Twenty participants who held senior leadership positions were interviewed using a semi-structured interview schedule. Due to social distancing regulations, the majority of the interviews were conduct via 45 minute zoom sessions. The data collected was analysed using Tesch's data analysis model. The method of data analysis applied was thematic analysis. The data collected was analysed using Tesch's data analysis model. The study findings include that the COVID-19 crisis has provided an opportunity for NPOs to strategise for growth opportunities and to rethink services and programmes. NPOs with poor crisis and risk management strategies and practices were most at risk of closure during the COVID-19 pandemic. However, NPOs have proved to have resilience in their ability to pivot and adapt services and programmes. Emotional support for staff combined with staff passion fostered a collective organisation culture of teamwork and commitment to their jobs despite the challenges and in some cases, reduced salaries. Integrating technology in service delivery was crucial for NPO survival. During a crisis, a hybrid model of online and face-to-face services can be provided and may be the new normal of rendering services. Donor fatigue is a concern considering the financial shocks from the external environment and marked by the economic downturn in light of the COVID-19 pandemic. The study concludes by providing five suggestions for future research, namely, 1) the cost-benefit of rendering services online, 2) donor fatigue, 3) Government support offered to NPOs during the COVID-19 pandemic, 4) compulsory COVID-19 vaccination in the workplace and 5) the integration of technology in poor socio-economic environment.